1993
DOI: 10.1103/physrevb.47.14823
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for initial quasilinearT21versus τ for Carr-Purcell-Meiboom-Gill NMR with diffusion and susceptibility differences in porous media and tissues

Abstract: Porous media containing Auids and subject to the field of an NMR instrument usually have incremental local magnetic fields due to susceptibility differences yd, such as between a Quid and a solid matrix. If yd~( (1 the effective variation co of the local precession angular frequency is limited to + zyzcoo, where coo is the mean precession angular frequency. Diffusion of Quid molecules through these local fields leads to a 7-dependent increase Rd in the value of 1/T2 obtained from Carr-Purcell-Meiboom-Gill (CPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 19 publications
2
70
0
Order By: Relevance
“…When we fitted Eqs. [10], [12], [15], and [16] in Microcal Origin, on average, the simulation data conformed to theory within a constant scaling factor of 6.67 Ϯ 0.44 when B 0 ⅐ ⌬ Ͻ 5 T. In addition, as expected from theory, we found the R* 2 Ͼ R 2 and the * Ͼ independent of the choice of parameters.…”
Section: Simulation Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…When we fitted Eqs. [10], [12], [15], and [16] in Microcal Origin, on average, the simulation data conformed to theory within a constant scaling factor of 6.67 Ϯ 0.44 when B 0 ⅐ ⌬ Ͻ 5 T. In addition, as expected from theory, we found the R* 2 Ͼ R 2 and the * Ͼ independent of the choice of parameters.…”
Section: Simulation Resultssupporting
confidence: 80%
“…In addition, if the field variations are weak, it is possible to approximate Eq. [5] with the second moment as a function of time (15,16). In this case, Eq.…”
Section: Parameters Affecting the Rate Of Decay Of The Mr Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…This expression can include a third term, to account for the effect of internal field gradients (G) on the diffusing hydrogen nuclei [Brown and Fantazinni, 1993]. However, in this study we found experimentally that G was negligible, so (4) describes the NMR response of our samples.…”
Section: Nmr Relaxationmentioning
confidence: 56%
“…Given the inhomogeneous nature of the electronic texture [33,34], an internal magnetic field gradient ∇B could originate from a spatial inhomogeneity of the spin susceptibility χ or, equivalently, of the local magnetization χ H [35,36]. Hence, ∇B χ H/2a, where 2a defines a typical domain size [35].…”
Section: Discussionmentioning
confidence: 99%